2002
DOI: 10.1002/bies.10125
|View full text |Cite
|
Sign up to set email alerts
|

Regulation by transcription attenuation in bacteria: how RNA provides instructions for transcription termination/antitermination decisions

Abstract: Regulation of gene expression by premature termination of transcription, or transcription attenuation, is a common regulatory strategy in bacteria. Various mechanisms of regulating transcription termination have been uncovered, each can be placed in either of two broad categories of termination events. Many mechanisms involve choosing between two alternative hairpin structures in an RNA transcript, with the decision dependent on interactions between ribosome and transcript, tRNA and transcript, or protein and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
211
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(214 citation statements)
references
References 37 publications
(36 reference statements)
1
211
0
1
Order By: Relevance
“…If no suitable primers were found, we extended the amplified region to 300 bp into each ORF. For AAB promoters known to contain leader peptides 28 , the promoter region included the leader peptide coding region. We designed each of the two primers with either XhoI or BamHI restriction sites.…”
Section: Methodsmentioning
confidence: 99%
“…If no suitable primers were found, we extended the amplified region to 300 bp into each ORF. For AAB promoters known to contain leader peptides 28 , the promoter region included the leader peptide coding region. We designed each of the two primers with either XhoI or BamHI restriction sites.…”
Section: Methodsmentioning
confidence: 99%
“…Expression of the at operon is controlled by tandem transcription and translation regulatory mechanisms based on sensing the level of charged͞uncharged tRNA Trp (17). Transcription of the structural genes of the at operon is regulated via the T-box transcription antitermination mechanism, where elevated levels of uncharged tRNA Trp induce transcription of rtpA (18), leading to AT production and increased trp operon expression and tryptophan biosynthesis (19). Translational control of at operon expression is provided by the ability of a translating ribosome to move along the mRNA region encoding a tryptophan-rich leader peptide.…”
mentioning
confidence: 99%
“…Until recently it was accepted (Goldberger, 1974;Serfling, 1989) that this mechanism involved proteins specified by a given structural gene of the operon acting as a regulatory macromolecule. But during the last decade it has been demonstrated that RNA molecules can also serve as transcriptional enhancers and repressors (Henkin & Yanofsky, 2002). Riboswitches in the paradigms of genetic regulation in eukaryotes and prokaryotes are presently being subjected to intense investigation (Hesselberth & Ellington, 2002;Le Hir et al, 2003;Nudler & Mironov, 2004).…”
Section: Discussionmentioning
confidence: 99%